Pendayagunaan Wakaf Produktif - Moh. Shobari Lubis; Abbas Sofwan Matlail Fajar (ADALAH, 2022)
Productive waqf, also known as misti'mâry waqf, capitalizes on Islamically permissible goods and services. Benefits become mauqûf and usable after the product or service is finished. Productive denotes result, work, goods, or stuff produced. This definition defines productivity as something that can generate. Waqf funds are maximized to serve the common welfare. Thus, empowerment strengthens social and economic positions to increase shared welfare through empowering individuals through waqf money for production companies. Productive waqf manages public waqf donations by producing them to create a sustainable surplus. Waqf contributions can be cash, precious metals, land, or buildings. This productive waqf surplus provides long-term funds for education, health, and communal welfare.